1978
DOI: 10.1002/1097-4679(197801)34:1<4::aid-jclp2270340102>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of unilateral and bilateral ECT on verbal and visual spatial memory

Abstract: Investigated the effects of unilateral left (UL), unilateral right (UR), and bilateral (B) ECT on the performance of right-handed male patients on the Wechsler Memory Scale and two tests of the Williams battery, which provided eight independent measures of verbal memory and two of visual-spatial memory. Patients were tested three times: (1) within 1 week prior to ECT; (2) within 30 minutes after the sixth ECT; (3) 10 days after the sixty ECT. Double blind procedures were maintained carefully. Results showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Early comparisons included the following: RUL‐Lancaster and LUL‐Lancaster in 12 studies, RUL‐Halliday and LUL‐Halliday in three studies , one comparison between RUL‐McAndrew and LUL‐McAndrew and one unspecified comparison between RUL and LUL . RUL temporo‐parietal was compared with LUL temporo‐parietal in five studies, with RUL fronto‐temporal in two studies, with RUL fronto‐parietal in 2 studies and one case report and with RUL fronto‐frontal in four studies (see Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Early comparisons included the following: RUL‐Lancaster and LUL‐Lancaster in 12 studies, RUL‐Halliday and LUL‐Halliday in three studies , one comparison between RUL‐McAndrew and LUL‐McAndrew and one unspecified comparison between RUL and LUL . RUL temporo‐parietal was compared with LUL temporo‐parietal in five studies, with RUL fronto‐temporal in two studies, with RUL fronto‐parietal in 2 studies and one case report and with RUL fronto‐frontal in four studies (see Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of these assessments were administered within a few minutes to a few days following treatment, and it is therefore unclear to what degree any verbal dysfunction persists. Halliday et al and Cronin et al found that patients receiving LUL ECT were still impaired on tests of verbal memory 4+ weeks post‐treatment; conversely, Jackson found that all verbal decrements had resolved by 10 days post‐treatment, and Chatterjee et al found no difference in memory scores between electrode placement groups after 3 weeks.…”
Section: Discussionmentioning
confidence: 98%
“…Jackson (1978) randomized 46 male right‐handed patients of unspecified diagnoses to BL, RUL, LUL ECT, or a no‐ECT control group. Thirty minutes after the sixth treatment, all ECT groups showed a decline in verbal and nonverbal memory scores compared to the control group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In seven other studies, either statistically insignificant or small mean differences between bilateral and nondominant unilateral ECT were found using memory tasks that made verbal processing difficult (1,5,10,20,24,27,28). In their study, recognition of common objects was worse following bilateral than nondominant unilateral ECT.…”
Section: Nonverbal Memorymentioning
confidence: 89%